(untitled) (Journal of actual problems of jurisprudence, 2016)
In state rassmotreny civil law provisions on the right to the brand name, draws attention to those that are essential when deciding on a violation of the right to trade, identifying similarities brand names confusingly. The article highlights the legislative provisions which must necessarily be the basis for determining the existence of violations of the right to the company name.